Exploring incivility as experienced by faculty and staff of Silliman University - Valbuena, Michele Joan D. (Silliman Journal, 2022)
Incivility in the workplace has become of interest in industrial/ organizational psychology research to understand employee welfare and design programs to develop employee wellbeing. A mixed method design was employed with faculty and staff at a private university in Central Philippines; a survey questionnaire was administered to measure their experiences of incivility and how these were related to their levels of burnout. While generally the faculty and staff reported not experiencing incivility and not associated with their average-to-low levels of burnout, the qualitative interviews indicated that respondents did not only experience incivility but also bullying. It was found that the faculty and staff of Silliman University did not understand what incivility really was, misconstruing the behaviors as bullying, hence the inconsistency on the data between the quantitative and qualitative researches. It is recommended that another survey study be done with a more robust research procedure.